2013
DOI: 10.4236/ojmh.2013.33018
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Infiltration, Capillary Barrier and Sloping Layered Soil on Flow and Solute Transfer in a Heterogeneous Lysimeter

Abstract: This aim of this paper is to describe a study of the combined effect of infiltration, capillary barrier and sloping layered soil on both flow and solute transport processes in a large, physical model (1 × 1 × 1.6 m3) called LUGH (Lysimeter for Urban Groundwater Hydrology) and a 3D numerical flow model. Sand and a soil composed of a bimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…A portion of flow arriving at the interface between the two materials is deflected along the slope producing simultaneously an increase in volumetric water content at the interface (Figure 3a). Bien et al, (2013) found similar results for studies in the same lysimeter.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
See 3 more Smart Citations
“…A portion of flow arriving at the interface between the two materials is deflected along the slope producing simultaneously an increase in volumetric water content at the interface (Figure 3a). Bien et al, (2013) found similar results for studies in the same lysimeter.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…This proportion is chosen to ensure the bi-modality of particle size in the mixture. The sizes of the three materials are similar to those observed in the most common lithofacies encountered in East Lyon (Prédélus et al, 2014a;Bien et al, 2013;Goutaland et al, 2008Goutaland et al, . 2013 (Figure 1a).…”
Section: Methodsmentioning
confidence: 50%
See 2 more Smart Citations
“…The choice of materials was made to replicate a glaciofluvial type soil similar to that observed in an unsaturated zone, in the region of Lyon (France) [22] [23]: that is to say, having the same particle size distribution and the same chemical composition ( Table 1). The selected materials are sand (0 -0.2 cm) and gravel (0.4 -1.1 cm) with which a bimodal mixture, which was formed in mass fraction 50% -50% (Figure 1).…”
Section: Methodsmentioning
confidence: 99%